Determinants of Household Income Changes Following Agricultural Land-Use Conversion in Gununghalu, Indonesia - Maura Zhafira Putri; Dini Rochdiani; Sara Ratna Qanti; Nur Syamsiyah (Universitas Negeri Gorontalo, 2026)
Economic challenges and specific policies often trigger land conversion in the countryside. The primary objective of this study is to explore the repercussions of land use change on household income and determine which household types are most vulnerable to the decline in income due to land use changes. The study was carried out in Gununghalu sub-district and used a quantitative approach. Surveys were conducted to collect data, which was subsequently evaluated through multivariate analysis using multiple linear regression to examine the significance of various socioeconomic factors on household income after land conversion. The results showed a positive and significant impact of land area, education, and age on income. In contrast, the number of commodities cultivated exerted a substantial negative influence, although involvement in farmer groups and the number of family dependents shown no significant effect. An other significant conclusion was that households overseeing an excessive number of commodities often encountered reduced revenue, attributed to their constrained ability to manage excessively diversified enterprises. Consequently, non-selective diversification measures may impose a burden on households. This study emphasizes the significance of capacity-oriented agricultural planning and enhancing access to education and land tenure in mitigating the dynamics of land use change.